Security monitor using Java mobile agent - Lee, Chit Boon. (2008)
This report investigates at how Java and Mobile Agent technology can be used to implement a generic distributed security monitor system for a large and distributed network. The proposed system consists of 4 sub-systems, namely, Client, Intelligent Server, Repository and Mobile Agent. As the design is component-based, new component or functionality added with minimal impact on the existing component. It is important for a good security monitor system to be updated regularly so that it is able to detect new security threat.